2001
DOI: 10.1152/ajpregu.2001.281.1.r133
|View full text |Cite
|
Sign up to set email alerts
|

Higher skeletal muscle protein synthesis and lower breakdown after chemotherapy in cachectic mice

Abstract: The influence of cancer cachexia and chemotherapy and subsequent recovery of skeletal muscle protein mass and turnover was investigated in mice. Cancer cachexia was induced using colon 26 adenocarcinoma, which is characteristic of the human condition, and can be cured with 100% efficacy using an experimental nitrosourea, cystemustine (C(6)H(12)CIN(3)O(4)S). Reduced food intake was not a factor in these studies. Three days after cachexia began, healthy and tumor-bearing mice were given a single intraperitoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…Six weeks after surgical resection of the primary tumor, muscle protein synthetic responses to feeding and leg proteolysis had returned to normal with additional decreases in lean leg mass, which was a disparity that we believe to be attributable to the now spent surgical insult (43). With a greater understanding of the processes at work in the skeletal muscle of cancer patients (in different cancers and at different stages), it may be possible to better tailor future therapies to both stimulate MPS, under fasted and fed conditions, and reduce MPB to combat the serious problem of cancer cachexia.…”
Section: Discussionmentioning
confidence: 83%
“…Six weeks after surgical resection of the primary tumor, muscle protein synthetic responses to feeding and leg proteolysis had returned to normal with additional decreases in lean leg mass, which was a disparity that we believe to be attributable to the now spent surgical insult (43). With a greater understanding of the processes at work in the skeletal muscle of cancer patients (in different cancers and at different stages), it may be possible to better tailor future therapies to both stimulate MPS, under fasted and fed conditions, and reduce MPB to combat the serious problem of cancer cachexia.…”
Section: Discussionmentioning
confidence: 83%
“…In mice bearing the MAC-16 adenocarcinoma, muscle loss is due to the combination of reduced synthesis and increased degradation [37]. Similarly Samuels et al demonstrated reduced protein synthesis and increased degradation in skeletal muscle co-incident with the onset of cachexia in mice implanted with the C26 murine model [38].…”
Section: Discussionmentioning
confidence: 92%
“…It has been recently reported that mice administered cystemustine experience a transient reduction of muscle protein synthesis rates [37]. In contrast, novel findings have shown that chemotherapeutic regimens decrease muscle protein breakdown rates in both controls and tumor-bearing animals.…”
Section: Muscle Wasting In Sepsis and Cancer Cachexiamentioning
confidence: 99%